SynapsEM: Computer-Assisted Synapse Morphometry - Watanabe, Shigeki; Davis, M. Wayne; Kusick, Grant F.; Iwasa, Janet; Jorgensen, Erik M. (Frontiers in Synaptic Neuroscience, 2020)
The structural features of a synapse, in part, determine its output. Synapses are extremely small and tightly packed with vesicles and other organelles. Visualizing synaptic structure requires imaging by electron microscopy, and the features in micrographs must be quantified using morphometry. Three parameters are typically assessed from each specimen: 1) the sizes of individual vesicles and organelles, 2) the absolute number and densities of organelles, and 3) distances between organelles and key features at synapses such as active zone membranes and dense projections. For data to be valid, the analysis must be repeated from hundreds or thousands of images from several biological replicates, a daunting task. Here we report a custom computer program to analyze these features: SynapsEM. In short, we developed macros for ImageJ/Fiji to record x,y-coordinates of segmented structures; the coordinates are then exported as text files. Independent investigators can reload the images and text files to confirm or re-evaluate the segmentation using ImageJ. The Matlab program calculates and reports key synaptic parameters from the coordinates. Since the values are calculated, rather than measured from each micrograph, other parameters can be extracted in Matlab by additional scripting. Thus, this program can accelerate morphometry of synapses and promote a more comprehensive analysis of synaptic ultrastructure.